Running reduces stress and enhances cell genesis in aged mice - Kannangara, Timal S. (Neurobiol Aging, 2010)
Cell proliferation and neurogenesis are diminished in the aging mouse dentate gyrus. However, it is not known whether isolated or social living affects cell genesis and stress levels in old animals. To address this question, aged (17–18 months old) female C57Bl/6 mice were single or group housed, under sedentary or running conditions. We demonstrate that both individual and socially housed aged C57Bl/6 mice have comparable basal cell proliferation levels and demonstrate increased running-induced cell genesis. To assess stress levels in young and aged mice, corticosterone (CORT) was measured at the onset of the active/dark cycle and 4 h later. In young mice, no differences in CORT levels were observed as a result of physical activity or housing conditions. However, a significant increase in stress in socially housed, aged sedentary animals was observed at the onset of the dark cycle; CORT returned to basal levels 4 h later. Together, these results indicate that voluntary exercise reduces stress in group housed aged animals and enhances hippocampal cell proliferation.